2020
DOI: 10.2147/ijwh.s258446
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Perceived Health Needs of Primiparous Mothers Referring to Primary Health Care Centers: A Qualitative Study</p>

Abstract: Background: Since the first step in meeting the health needs of primiparous women involves understanding their conditions, the present study aimed to determine the health needs of primiparous women from their own viewpoints. Methods: This study had a qualitative approach based on the conventional qualitative content analysis method, in which the purposive sampling method was used. Data were collected by semi-structured interviews. Data saturation was achieved by interviewing 12 participants. To ensure the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Primiparous women have to deal with insecurity, need for mastery and role definition, while women that have more children are concerned about how to appropriately divide time between their children (Haga, Lynne, Slinning, & Kraft, 2012; Krieg, 2007). Similarly, primiparous women need more support from relatives and healthcare workers (Salarvand, Mousavi, Esmaeilbeigy, Changaee, & Almasian, 2020). Thus, the different concerns or needs of first-time mothers and multiparous mothers may hold the key to creating differentiated preventive interventions for each, instead of grouping them together.…”
Section: Discussionmentioning
confidence: 99%
“…Primiparous women have to deal with insecurity, need for mastery and role definition, while women that have more children are concerned about how to appropriately divide time between their children (Haga, Lynne, Slinning, & Kraft, 2012; Krieg, 2007). Similarly, primiparous women need more support from relatives and healthcare workers (Salarvand, Mousavi, Esmaeilbeigy, Changaee, & Almasian, 2020). Thus, the different concerns or needs of first-time mothers and multiparous mothers may hold the key to creating differentiated preventive interventions for each, instead of grouping them together.…”
Section: Discussionmentioning
confidence: 99%
“…Ashford (2016) found that nearly 49 percent of 21 million teenage pregnancies are unintended (Salarvand et al, 2020) with contextual factors such as the individual, interpersonal, community, and societal factors were contributing to the high rate. As low contraceptive use (Demirci & Bogen, 2017) among teenagers was a contributing factor, these high rates require initiatives to improve contraceptive acceptance.…”
Section: Literature Review Pregnancy Experiencementioning
confidence: 99%
“…Primiparous women experience the physical and psychological changes and challenges of pregnancy and motherhood for the first time. Being a primiparous mother has been linked to a higher risk of mental distress and difficulties with breastfeeding, 25 both of which have also been associated with increased infant regulatory problems. 26 Our findings suggest that perhaps the demands of becoming a first-time mother can compound the stressors experienced by some refugee mothers across the pre-migration and post-migration periods creating linked vulnerabilities that can affect infant regulation, even years after migration.…”
Section: The Counterfactual Mediation Analysis Was Consistent With Thementioning
confidence: 99%